(untitled) (Eureka Journal of Humanities and Social Research, 2025)
In the 21st century, the processes of global digitalization and the expansion of e-commerce are fundamentally changing the form and content of economic relations. Trade through Internet platforms, the introduction of online payment systems, digital banking services not only ease people’s lives, but also create conditions for the commission of new types of offenses through these systems. In particular, among such criminal activities as untraditional financial fraud, money laundering in digital networks, crimes involving virtual property, the phenomenon of "droppin" is manifested as a particularly dangerous socio-legal phenomenon [1].